ナンキョク カンソクセン シラセ デ エラレタ センジョウ ジュウリョク データ ノ セイビ - 小西, 康夫; コニシ, ヤスオ; 福田, 洋一; フクダ, ヨウイチ; 野木, 義史; ノギ, ヨシフミ; Konishi, Yasuo; Fukuda, Yoichi; Nogi, Yoshifumi (2006)
P(論文) 砕氷船「しらせ」船不での重力測定は,第27次南極地域観測隊以来,継続実施されており,およそ17年分のデータが蓄積されている.この内,第27次隊から第33次隊のデータについては,すでに処理されたMGD77フォーマットのデータが提供されていたが,第34次隊以降のデータについては,統一的なデータ処理がされないままの状態であった.そこで,今回,第34次隊から第46次隊の間に得られたデータについて新たにデータ処理を実施し,重力異常データを作成した.この際,特に長波長域での重力データの精度向不のため,第27次隊以降のすべてのデータについて衛星高度計による海域重力異常を基準としたドリフト補正を行った.ここでは,これらの処理の概要ならびに得られたデータセットの状況について報告する. A ship-borne gravity survey on board the icebreaker Shirase has been continuously conducted since JARE-27 (the 27th Japanese Antarctic Research Expedition); about 17 years of gravity data have been accumulated. Although data obtained from JARE-27 to JARE-33 have already been processed and stored in MGD77 format, data starting with JARE-34 have remained unprocessed. We newly processed the data from JARE-34 to JARE-46 to obtain free-air gravity anomalies. To attain better quality, especially in the long wavelength gravity signals, we also applied drift corrections for all the data sets since JARE-27 by employing satellite derived gravity anomalies as a reference gravity field. This report summarizes the data processing and the status of the surface ship gravity data. departmental bulletin paper